MODERN FACTORS FOR RAISING STUDENT-YOUTH INNOVATIVE THINKING IN THE HIGHER EDUCATION - Abdurahmonov Hasan Ibrohimovich (American Journals, 2023)
The development of an innovational strategy is the main focus of its development in the first half of the 21st century. In such conditions, it is necessary to develop a system of holistic views, which will become the philosophical basis for the formation of the country's strategy for innovation development. Such a holistic system, in our opinion, should be based on a worldview pose, within which a person is recognized as the main source of any development, and at the same time is always the result of achieved social relations.
Keywords: Development, innovational strategy, innovation, holistic views, youth, innovation thinking.